The effect of mindfulness therapy through an android application on nurses' work stress: A literature review - Triyanto Triyanto; Ridlwan Kamaluddin (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Introduction: Several studies have shown that nurses have high levels of work stress. Work stress can be overcome with therapy, especially mindfulness therapy. The purpose of this literature review is to synthesize the literature on mindfulness therapy to reduce work stress for nurses.Objectives : The formulation of the problem in this study is how to influence mindfulness therapy through an android applicationon work stress on work nurses in Emergency Room.Methods: Literature search was carried out using several databases, including PubMed and Scient Direct. The keywords used are different in each database. For Pubmed use "mindfulness" and "online" and "workload" or "work stress" or "occupational stress" and “nurse”, meanwhile for scient direct use "mindfulness" and "online" or "app" and "workload" or "work stress" or "occupational stress" and "RCT". Results: The search results from various literature obtained 360 articles, then through a series of selections, 67 match the criteria. These articles are publications from 2018 – 2023. but only 7 articles that are reviewed and in accordance with the research topic  and 2 articles not available cannot be accessed, 1 article another language. There were 4 selected articles left for review. Conclusions: Nurses work have a high level of stress associated with a large workload. Work stress that is not handled properly can lead to social dysfunction and somatic disorders. Mindfulness-based stress reduction therapy is known effective in reducing the level of nurses anxiety, work fatigue, and work stress. Direct application or online is safe to give, because it does not have significant difference in effectiveness.